(untitled) - Evert, Christine

Calprotectin (S100A8/A9) as a marker of inflammation and treatment monitoring in cases of juvenile idiopathic arthritis in the Western Cape, South Africa (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.